Vegetation dynamics associated with changes in atmospheric nitrogen deposition and climate in hardwood forests of Shenandoah and Great Smoky Mountains National Parks, USA. (June 2018) - McDonnell, T.C.; Belyazid, S.; Sullivan, T.J.; Bell, M.; Clark, C.; Blett, T.; Evans, T.; Cass, W.; Hyduke, A.; Sverdrup, H.
Abstract: Ecological effects of atmospheric nitrogen (N) and sulfur (S) deposition on two hardwood forest sites in the eastern United States were simulated in the context of a changing climate using the dynamic coupled biogeochemical/ecological model chain ForSAFE-Veg. The sites are a mixed oak forest in Shenandoah National Park, Virginia (Piney River) and a mixed oak-sugar maple forest in Great Smoky Mountains National Park, Tennessee (Cosby Creek). The sites have received relatively high levels of both S and N deposition and the climate has warmed over the past half century or longer. The model was used to evaluate the composition of the understory plant communities, the alignment between plant species niche preferences and ambient conditions, and estimate changes in relative species abundances as reflected by plant cover under various scenarios of future atmospheric N and S deposition and climate change. The main driver of ecological effects was soil solution N concentration. Results of this research suggested that future climate change might compromise the capacity for the forests to sustain habitat suitability. However, vegetation results should be considered preliminary until further model validation can be performed. With expected future climate change, preliminary estimates suggest that sustained future N deposition above 7.4 and 5.0 kg N/ha/yr is expected to decrease contemporary habitat suitability for indicator plant species located at Piney River and Cosby Creek, respectively. Graphical abstract: Image 1 Highlights: Climate and N deposition are major drivers of plant diversity. We evaluate impacts on biodiversity using a soil-plant model chain. Compositional changes were mostly driven by changes in soil solution N availability. Anticipated climate change exacerbated the effects of N deposition. Abstract : Simulated climate change and N deposition affected habitat suitability and interacted with changes in soil chemistry.